Financial Investment Behavior of Individual Investors in Indonesia After the Revocation of the Covid-19 Policy - Thasrif Murhadi; Ghazali Syamni; Marzuki Marzuki; Zamzami Zainuddin; Sari Yulis Terfiadi (Faculty of Economics and Business Udayana University, 2023)
This study explores the impact of psychological, social, and demographic aspects on individual stock investor decision-making after the revocation of COVID-19 in Indonesia. With the cooperation of local representatives of the Indonesian Stock Exchange, this study uses data collection approaches such as sending questionnaires to participants. The questionnaires were sent out between the three weeks of January 2023 after President Joko Widodo announced the lifting of social restrictions during the pandemic, and then at the end of 2022. In this way, 108 questionnaire responses were thus collected for the study. The results showed that individual stock investor behavior gender, age, and marital status didn’t affect individual investor's investment behavior. Work, education, and experience positively and significantly impact an individual investor's investment behavior. However, the revocation of social constraints negatively affects this behavior. A study finds education is the most important variable influencing equity investor behavior. Keyword: Behavior; Covid-19; Investors; Individuals.